1990
DOI: 10.1002/jez.1402550110
|View full text |Cite
|
Sign up to set email alerts
|

Testicular response to melatonin or suprachiasmatic nuclei ablation in the spotted skunk

Abstract: Testes of the Western spotted skunk enlarge and regress seasonally. The pineal hormone, melatonin, may be important in timing this seasonal reproductive activity. Likewise, the suprachiasmatic nuclei (SCN) have been implicated as possible neural regulators of pineal and reproductive events. These experiments were conducted to determine whether ablation of the SCN or constant administration of melatonin alters timing of the seasonal pattern of testicular regression and recrudescence. Male skunks (n = 24) were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Testicular function in western spotted skunks exhibits seasonal variation. The seasonal changes in testis size reported in this study agree with previous results in this species (Mead, 1968a;Berria et al, 1990), the greatest testis size being observed during the autumn breeding season. The peak in mean testis size was approximately twice the basal size.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Testicular function in western spotted skunks exhibits seasonal variation. The seasonal changes in testis size reported in this study agree with previous results in this species (Mead, 1968a;Berria et al, 1990), the greatest testis size being observed during the autumn breeding season. The peak in mean testis size was approximately twice the basal size.…”
Section: Discussionsupporting
confidence: 92%
“…The western spotted skunk, Spilogale gracilis, is a seasonally breeding mammal; the testes reach maximal weight and most copulations occur in late September and early October (Mead, 1968a). Testicular recrudescence occurs from July to October in skunks maintained on a natural photoperiod (Berria et al, 1990) and the pineal gland is considered to be involved in entraining this testicular cycle. Other attributes of the male reproduc¬ tive cycle, such as seminal characteristics and testosterone concentrations, have not been reported for this species. Electroejaculation has been used successfully to obtain semen from a few mustelid carnivores including domestic ferrets, Mustek putorius (Shump et al, 1976;Atherton et al, 1989;Wildt et al, 1989), black-footed ferrets, Mustela nigripes (Kitchin et al, 1988; Curry et al, 1989), and mink, Mustek vison (Aulerich et al, 1972).…”
Section: Introductionmentioning
confidence: 99%